Clinical and laboratory evaluation of premature goat kids with and without antenatal corticotherapy - Braga, Gabriel Isola [UNESP]; Alcindo, Jefferson Filgueira [UNESP]; Narciso, Luis Gustavo [UNESP]; Bovino, Fernanda [UNESP]; Trein, Thomas Alexander [UNESP]; Trevizan, Juliane Teramachi [UNESP]; Ferraz, Murilo Catelani [UNESP]; Formiga Feitosa, Francisco Leydson [UNESP] (Univ Federal Santa Maria, 2022)
This article evaluated the vital parameters. blood gas measurements. cortisol values and radiological findings of goat kids born at term and prematurely (hiring the first 48 hours of life. For this purpose. 24 kids from 24 goats were used and assigned to groups as follows: Group I, eight kids born through cesarean sections performed at 149 days of gestation; Group II, eight kids born through cesarean sections performed at 143 days of gestation; Group III, eight kids born through cesarean sections performed at 143 days of gestation. whose mothers received 20 mg of dexamethasone. Group I had lower heart rate values than the other groups at 60 minutes after birth. In terms of temperature, there was no difference between the groups. The pH values were reduced shortly after birth. rising at 24 and 48 hours in all animals studied. In terms of the cortisol levels, the values increased significantly at birth (M0), with the highest values obtained in animals in group II. These values decreased at 48 hours after birth in the evaluated goats. The animals belonging to group I showed better radiographic aspects, and throughout the 48 hours of evaluation, all newborns exhibited adequate respiratory adaptation. It can be concluded that antenatal dexamethasone administered at 143 days of gestation did not influence neonatal viability. metabolic or radiographic parameters. The metabolic changes found are consistent with the extrauterine adaptation period that animals in this stage of life.
Keywords: lung maturity; blood gas analysis; neonates; goats